Belatacept Rescue Therapy in Kidney Transplant Recipients With Vascular Lesions: A Case Control Study. Issue 11 (2nd September 2017) - Bertrand, D.; Cheddani, L.; Etienne, I.; François, A.; Hanoy, M.; Laurent, C.; Lebourg, L.; Le Roy, F.; Lelandais, L.; Loron, M. C.; Godin, M.; Guerrot, D.
Abstract : Immunosuppression in kidney transplant recipients with decreased graft function and severe histological vascular changes can be particularly challenging. Belatacept could be a valuable option, as a rescue therapy in this context. We report a retrospective case control study comparing a CNI to belatacept switch in 17 patients with vascular damage and low eGFR to a control group of 18 matched patients with CNI continuation. Belatacept switch was performed on average 51.5 months after kidney transplantation (6.2–198 months). There was no difference between the two groups regarding eGFR at inclusion, and 3 months before inclusion. In the "CNI to belatacept switch group, " mean eGFR increased significantly from 23.5 ± 6.7 mL/min/1.73m 2 on day 0, to 30.4 ± 9.1 mL/min/1.73 m 2 on month 6 (p < 0.001) compared to the control group, in which no improvement was observed. These results were still significant on month 12. Two patients experienced biopsy‐proven acute rejection. One was effectively treated without belatacept discontinuation. Two patients needed belatacept discontinuation for infection. In conclusion, the remplacement of CNI with belatacept in patients with decreased allograft function and vascular lesions is associated with an improvement in eGFR. Abstract : Replacement of calcineurin inhibitors with belatacept in patients with decreased allograft function and vascular lesions is associated with an improvement in eGFR compared with an ongoing conventional strategy with calcineurin inhibitors.